Urban Pests and Pest Management - Philip G. Koehler (EDIS)
The warm southern states provide an ideal environment for a wide variety of pests — and because almost everyone has problems with pests, most urban areas are sprayed with pesticides. 30 to 40 percent of pesticide use is in urban areas, but most pesticide applications are unnecessary and can result in environmental contamination and human exposure to pesticides. This 5-page fact sheet from Pests in and around the Southern Home (SP486) introduces integrated pest management practices that can help reduce pesticide use in the home. Written by P.G. Koehler and published by the UF Department of Entomology and Nematology, October 2013.